EXPLORING ISLAMIC PSYCHOLOGY CONCEPTS IN ENHANCING THE LEARNING MOTIVATION OF ENTREPRENEURSHIP STUDENTS - Permadi, Adi; Wantini (International Journal of Multidisciplinary Reseach, 2025)
Learning motivation is a fundamental element in the success of higher education, especially in entrepreneurship courses that require creativity, innovation, courage to take risks, and mental toughness. This study aims to analyze the contribution of Islamic psychology concepts in increasing student learning motivation in entrepreneurship learning in Islamic higher education institutions. This study uses a descriptive qualitative method through classroom observation, semi-structured interviews, and learning reflections on students from eight undergraduate programs at Ahmad Dahlan University, namely Psychology, Law, Information Systems, Food Technology, English Literature, Biology, Pharmacy, and Medicine. The results of the study indicate that the integration of Islamic psychological values, including fitrah, religious motivation, tazkiyatun nafs, work ethics, and the concept of ikhtiar tawakal, plays a significant role in increasing student learning motivation, both quantitatively (discipline, participation, and project completion) and qualitatively (deepening the meaning of learning, work ethic, courage to innovate, and resilience in the face of failure). A relatively consistent positive response was found in all study programs, but with nuances of internalization that differed according to the characteristics of each discipline. These findings emphasize the importance of developing an Islamic psychology-based entrepreneurial learning model to produce Muslim entrepreneurial graduates who are competent, have integrity, are resilient, and are oriented towards social benefit.